Directly Compressed Tablets of Free Acid Ibuprofen with Nanocellulose Featuring Enhanced Dissolution: A Side-by-Side Comparison with Commercial Oral Dosage Forms - Athanasios Mantas; Marie-Amélie Petit; Albert Mihranyan (MDPI AG, 2020)
We have previously reported that heated powder mixtures of ibuprofen (IBU) and high surface area nanocellulose exhibit an enhanced dissolution and solubility of the drug due to IBU amorphization. The goal of the present work was to further elaborate the concept and conduct side-by-side in vitro drug release comparisons with commercial formulations, including film-coated tablets, soft gel liquid capsules, and IBU-lysine conjugate tablets, in biorelevant media. Directly compressed tablets were produced from heated mixtures of 20% w/w IBU and high surface area Cladophora cellulose (CLAD), with 5% w/w sodium croscarmelose (AcDiSol) as superdisintegrant. The side-by side studies in simulated gastric fluid, fasted-state simulated intestinal fluid, and fed-state simulated intestinal fluid corroborate that the IBU-CLAD tablets show more rapid and less variable release in various media compared to three commercial IBU formulations. On the sidelines of the main work, a possibility of the presence of a new meta-crystalline form of IBU in mixture with nanocellulose is discussed.